TINDAK TUTUR ILOKUSI PADA TEATER MODERN MALAM JAHANAM (TEATER SATIVA) - Sari Ramdhani, Intan; Khoironi, Rizka (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the illocutionary speech acts in each of the dialogues spoken by the characters in the performance of the Modern Malam Jahanam Theater (Theater Sativa) by playing a Realist Drama adaptation of a script from Motinggo Boesje's work entitled Malam Jahanam. This study uses a qualitative research with a descriptive approach. The data in this research is the video of the Modern Malam Jahanam Theater (Theatre Sativa). The source of the data taken is a Theater video uploaded in February 2021 with a duration of 44 minutes 28 seconds. The results of the study show that there are five types of illocutionary speech acts in this study: (1) Directive there are 8 dialogues which state the directive speech of ordering, inviting, asking, suggesting, challenging, and advising. (2) Expressiveness, there are 3 dialogues that express expressive speech, namely blaming, praising, and flattering. (3) There are 3 commissives, namely a promise, threatening, blaming. (4) There are 4 assertives, namely the words stating, complaining, reporting, and showing. (5) There are 2 declarative utterances in the dialogue, namely deciding and prohibiting.